From Maps to Models: Augmenting the Nation's Geospatial Intelligence Capabilities - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The United States faces numerous, varied, and evolving threats to national security, including terrorism, scarcity and disruption of food and water supplies, extreme weather events, and regional conflicts around the world. Effectively managing these threats requires intelligence that not only assesses what is happening now, but that also anticipates potential future threats. The National Geospatial-Intelligence Agency (NGA) is responsible for providing geospatial intelligence on other countries2014assessing where exactly something is, what it is, and why it is important2014in support of national security, disaster response, and humanitarian assistance. NGA's approach today relies heavily on imagery analysis and mapping, which provide an assessment of current and past conditions. However, augmenting that approach with a strong modeling capability would enable NGA to also anticipate and explore future outcomes. A model is a simplified representation of a real-world system that is used to extract explainable insights about the system, predict future outcomes, or explore what might happen under plausible what-if scenarios. Such models use data and\/or theory to specify inputs (e.g., initial conditions, boundary conditions, and model parameters) to produce an output. From Maps to Models: Augmenting the Nation's Geospatial Intelligence Capabilities describes the types of models and analytical methods used to understand real-world systems, discusses what would be required to make these models and methods useful for geospatial intelligence, and identifies supporting research and development for NGA. This report provides examples of models that have been used to help answer the sorts of questions NGA might ask, describes how to go about a model-based investigation, and discusses models and methods that are relevant to NGA's mission.

Next Generation Earth Systems Science at the National Science Foundation - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Science Foundation (NSF) has played a key role over the past several decades in advancing understanding of Earth's systems by funding research on atmospheric, ocean, hydrologic, geologic, polar, ecosystem, social, and engineering-related processes. Today, however, those systems are being driven like never before by human technologies and activities. Our understanding has struggled to keep pace with the rapidity and magnitude of human-driven changes, their impacts on human and ecosystem sustainability and resilience, and the effectiveness of different pathways to address those challenges. Given the urgency of understanding human-driven changes, NSF will need to sustain and expand its efforts to achieve greater impact. The time is ripe to create a next-generation Earth systems science initiative that emphasizes research on complex interconnections and feedbacks between natural and social processes. This will require NSF to place an increased emphasis on research inspired by real-world problems while maintaining their strong legacy of curiosity driven research across many disciplines 2013 as well as enhance the participation of social, engineering, and data scientists, and strengthen efforts to include diverse perspectives in research.

Fundamental Research in High Energy Density Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
High energy density (HED) science has critical applications for society from fusion energy to sustaining the US nuclear deterrent, while also contributing to broader scientific questions such as understanding planets and their origins. The next decade of HED science will be instrumental to growing our understanding and in the development of new technologies and processes. Fundamental Research in High Energy Density Science identifies key challenges and science questions for the field for the coming decade and proposes ways to address them.

Origins, Worlds, and Life: Planetary Science and Astrobiology in the Next Decade - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. This booklet highlights key science questions, identifies priority missions, and presents a research strategy that includes both planetary defense and human exploration.

Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.

Assessment of Commercial Space Platforms for Earth Science Instruments: Report Series—Committee on Earth Science and Applications from Space - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Space-based Earth observations enable global observations of the land surface, biosphere, solid Earth, atmosphere, cryosphere, and oceans. Earth observations from space, combined with data acquired from in situ and ground-based instruments, help scientists understand the components of the Earth system and their interactions and enable wide-ranging applications, including forecasts of weather and air quality, projections of future climate, management of natural resources, ecological forecasting, disaster management, drought and wildfire prediction, and the mapping and prediction of vector borne\/animal diseases. At the request of NASA Earth Science Division, this report assesses the potential use of a proposed multi-user, robot-tended, uncrewed commercial space platform as a potential host for a large number of Earth remote sensing instruments. Assessment of Commercial Space Platforms for Earth Science Instruments evaluates the utility and practicality of a platform in a Sun-synchronous orbit, capable of hosting 20 or more instruments.

Materials Science and Engineering in a Post-Pandemic World: A DoD Perspective: Proceedings of a Workshop - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Advances in materials science and engineering play a crucial role in supporting the U.S. economy and national security. To maintain its leading edge in the field, the United States relies on a rich and diverse innovation ecosystem encompassing industry, academic institutions, and government laboratories. While this ecosystem has generated numerous gains for defense agencies, the technology sector, consumers, and the country as a whole over many decades, recent years have brought new challenges and a shifting global dynamic in the field. The United States, long a global magnet for science, technology, engineering, and mathematics education and expertise, has seen its competitive edge slip as other countries in Europe and Asia have increased their investments in cultivating science and engineering talent and innovation. In 2020, the emergence of the COVID-19 pandemic caused far-reaching disruptions for both education and supply chains across the world, compounding many of the dynamics that were already affecting materials science and engineering in the United States. To explore these issues, the Workshop on Materials Science and Engineering in a Post-Pandemic World was organized as part of a workshop series on Defense Materials Manufacturing and Its Infrastructure. Hosted by the National Academies of Sciences, Engineering, and Medicine, the virtual event brought together approximately 30 speakers and attendees representing materials science, engineering, and manufacturing experts from industry, academia, and government agencies. The 3-day workshop explored education and workforce trends across the nation and the globe, with particular focus on the U.S. Department of Defense and university-government collaborations. Participants discussed how the COVID-19 pandemic has affected science and engineering education, opportunities to reimagine traditional education for the field, and the imperative to develop a more diverse workforce. Several speakers presented their views on what the post-pandemic future may hold, and many offered perspectives on key concerns and priorities for the field moving forward. This publication summarizes the presentations and discussion of the workshop.

Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The effective use of data science - the science and technology of extracting value from data - improves, enhances, and strengthens acquisition decision-making and outcomes. Using data science to support decision making is not new to the defense acquisition community; its use by the acquisition workforce has enabled acquisition and thus defense successes for decades. Still, more consistent and expanded application of data science will continue improving acquisition outcomes, and doing so requires coordinated efforts across the defense acquisition system and its related communities and stakeholders. Central to that effort is the development, growth, and sustainment of data science capabilities across the acquisition workforce. At the request of the Under Secretary of Defense for Acquisition and Sustainment, Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science assesses how data science can improve acquisition processes and develops a framework for training and educating the defense acquisition workforce to better exploit the application of data science. This report identifies opportunities where data science can improve acquisition processes, the relevant data science skills and capabilities necessary for the acquisition workforce, and relevant models of data science training and education.

Climate Intervention in an Earth Systems Science Framework: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
To consider how an Earth system science approach can inform research on climate intervention, The National Academies of Sciences, Engineering, and Medicine held a virtual workshop on June 20-22, 2023 titled Climate Intervention in an Earth Systems Science Framework. Individuals with a wide range of physical, ecological, and social sciences expertise explored climate interventions within the context of convergent research and the capacities of the National Science Foundation (NSF). The workshop drew on the National Academies report Next Generation Earth Systems Science at the National Science Foundation, which called upon NSF to pursue an Earth systems science initiative that emphasizes research on interconnections and feedback between natural and social processes; focuses on real-world problems; enhances the participation of social, engineering, and data scientists; and strengthens efforts to include diverse perspectives in research.

Foundations of a Healthy and Vital Research Community for NASA Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The U.S. space science community includes thousands of scientists across multiple disciplines that influence and are influenced by the many engineers, technicians, and support personnel that are part of the space research enterprise. Over one-third of NASA's budget is devoted to space science, and the agency currently operates over 50 space missions in the fields of astrophysics, Earth science, solar and space physics, planetary science, and the biological and physical sciences. The strength of NASA science lies with its people, both those who work directly for the agency and the thousands of researchers and professionals who are funded by NASA grants and contracts. At the request of NASA, this report examines the foundation for healthy and vital research communities. Foundations of a Healthy and Vital Research Community for NASA Science identifies the characteristics of a healthy and vital research community, defines implementable measures for assessing the health and vitality of a research community, describes the types of data that NASA should be collecting to enable future assessments of the health and vitality of the scientific work force, and recommends best practices to improve the health and vitality of NASA2019s research communities.

High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps: Proceedings of a Workshop-in Brief - Anne Johnson (The National Academies Press, 2023)
The U.S. Department of Defense faces a complex array of challenges in its efforts to retain a position of technological dominance and to protect national security. Several aspects of materials and manufacturing, especially the ability of materials to operate with predictable behaviors in high-temperature environments, pose particular challenges. To illuminate issues surrounding novel high-temperature materials discovery, development, manufacturing, and application, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps on May 10-11, 2022. This publication summarizes the presentations and discussion of the workshop.

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.

Roundtable on Data Science Postsecondary Education: A Compilation of Meeting Highlights - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Established in December 2016, the National Academies of Sciences, Engineering, and Medicine's Roundtable on Data Science Postsecondary Education was charged with identifying the challenges of and highlighting best practices in postsecondary data science education. Convening quarterly for 3 years, representatives from academia, industry, and government gathered with other experts from across the nation to discuss various topics under this charge. The meetings centered on four central themes: foundations of data science; data science across the postsecondary curriculum; data science across society; and ethics and data science. This publication highlights the presentations and discussions of each meeting.

Machine Learning and Artificial Intelligence to Advance Earth System Science: Opportunities and Challenges: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The Earth system - the atmospheric, hydrologic, geologic, and biologic cycles that circulate energy, water, nutrients, and other trace substances - is a large, complex, multiscale system in space and time that involves human and natural system interactions. Machine learning (ML) and artificial intelligence (AI) offer opportunities to understand and predict this system. Researchers are actively exploring ways to use ML\/AI approaches to advance scientific discovery, speed computation, and link scientific communities. To address the challenges and opportunities around using ML\/AI to advance Earth system science, the National Academies convened a workshop in February 2022 that brought together Earth system experts, ML\/AI researchers, social and behavioral scientists, ethicists, and decision makers to discuss approaches to improving understanding, analysis, modeling, and prediction. Participants also explored educational pathways, responsible and ethical use of these technologies, and opportunities to foster partnerships and knowledge exchange. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.

Improving the Intelligence Community's Leveraging of the Full Science and Technology Ecosystem - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The agencies within the U.S. Intelligence Community (IC) depend on advanced technology to achieve their goals. While AI, cloud computing, advanced sensors, and big data analytics will fundamentally change both the global threat landscape and IC tradecraft, advances from biology, chemistry, materials, quantum science, network science, social\/behavioral\/economic sciences, and other fields also have that potential. Maintaining awareness of advances in science and technology is more essential than ever, to avoid surprise, to inflict surprise on adversaries, and to leverage those advances for the benefit of the nation and the IC. This report explores ways in which the IC might leverage the future research and development ecosystem.

Airborne Platforms to Advance NASA Earth System Science Priorities: Assessing the Future Need for a Large Aircraft - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The National Aeronautics and Space Administration (NASA) and other U.S. science research agencies operate a fleet of research aircraft and other airborne platforms that offer diverse capabilities. To inform NASA's future investments in airborne platforms, this study examines whether a large aircraft that would replace the current NASA DC-8 is needed to address Earth system science questions, and the role of other airborne platforms for achieving future Earth system science research goals.

Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. New research will expand our understanding of our solar system's origins, how planets form and evolve, under what conditions life can survive, and where to find potentially habitable environments in our solar system and beyond. Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 highlights key science questions, identifies priority missions, and presents a comprehensive research strategy that includes both planetary defense and human exploration. This report also recommends ways to support the profession as well as the technologies and infrastructure needed to carry out the science.

Report Series: Committee on Biological and Physical Sciences in Space: Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
After several decades since the last human visit, NASA is planning to return to the Moon, this time not only to visit but also to carry out extensive scientific experiments, establish a habitat occupied by astronauts, and learn lessons that will help in preparations for the eventual establishment of a human presence on Mars. The Commercial Lunar Payload Services (CLPS) program, overseen by NASA, will provide transport to the Moon for scientists who want to carry out research on the lunar surface or in orbit around the Moon. Recognizing the need to introduce and explain the CLPS program to researchers, the Committee on Biological and Physical Sciences in Space of the National Academies of Sciences, Engineering, and Medicine held a workshop on March 24-25, 2021 entitled \

Research Opportunities in Corrosion Science and Engineering - National Research Council (The National Academies Press, 2011)
The field of corrosion science and engineering is on the threshold of important advances. Advances in lifetime prediction and technological solutions, as enabled by the convergence of experimental and computational length and timescales and powerful new modeling techniques, are allowing the development of rigorous, mechanistically based models from observations and physical laws. Despite considerable progress in the integration of materials by design into engineering development of products, corrosion considerations are typically missing from such constructs. Similarly, condition monitoring and remaining life prediction (prognosis) do not at present incorporate corrosion factors. Great opportunities exist to use the framework of these materials design and engineering tools to stimulate corrosion research and development to achieve quantitative life prediction, to incorporate state-of-the-art sensing approaches into experimentation and materials architectures, and to introduce environmental degradation factors into these capabilities. Research Opportunities in Corrosion Science and Engineering identifies grand challenges for the corrosion research community, highlights research opportunities in corrosion science and engineering, and posits a national strategy for corrosion research. It is a logical and necessary complement to the recently published book, Assessment of Corrosion Education, which emphasized that technical education must be supported by academic, industrial, and government research. Although the present report focuses on the government role, this emphasis does not diminish the role of industry or academia.

Exoplanet Science Strategy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The past decade has delivered remarkable discoveries in the study of exoplanets. Hand-in-hand with these advances, a theoretical understanding of the myriad of processes that dictate the formation and evolution of planets has matured, spurred on by the avalanche of unexpected discoveries. Appreciation of the factors that make a planet hospitable to life has grown in sophistication, as has understanding of the context for biosignatures, the remotely detectable aspects of a planet's atmosphere or surface that reveal the presence of life. Exoplanet Science Strategy highlights strategic priorities for large, coordinated efforts that will support the scientific goals of the broad exoplanet science community. This report outlines a strategic plan that will answer lingering questions through a combination of large, ambitious community-supported efforts and support for diverse, creative, community-driven investigator research.